Study protocol of the randomised placebo-controlled GLOBE trial: GLP-1 for bridging of hyperglycaemia during cardiac surgery. Issue 6 (4th June 2018) - Hulst, Abraham H; Visscher, Maarten J; Godfried, Marc B; Thiel, Bram; Gerritse, Bas M; Scohy, Thierry V; Bouwman, R Arthur; Willemsen, Mark G A; Hollmann, Markus W; DeVries, J Hans; Preckel, Benedikt; Hermanides, Jeroen
Abstract : Introduction: Perioperative hyperglycaemia is common during cardiac surgery and associated with postoperative complications. Although intensive insulin therapy for glycaemic control can reduce complications, it carries the risk of hypoglycaemia. GLP-1 therapy has the potential to lower glucose without causing hypoglycaemia. We hypothesise that preoperative liraglutide (a synthetic GLP-1 analogue) will reduce the number of patients requiring insulin to achieve glucose values<8 mmol l -1 in the intraoperative period. Methods and analysis: We designed a multi-centre randomised parallel placebo-controlled trial and aim to include 274 patients undergoing cardiac surgery, aged 18–80 years, with or without diabetes mellitus. Patients will receive 0.6 mg liraglutide or placebo on the evening before, and 1.2 mg liraglutide or placebo just prior to surgery. Blood glucose is measured hourly and controlled with an insulin bolus algorithm, with a glycaemic target between 4–8 mmol l −1 . The primary outcome is the percentage of patients requiring insulin intraoperatively. Ethics and dissemination: This study protocol has been approved by the medical ethics committee of the Academic Medical Centre (AMC) in Amsterdam and by the Dutch competent authority. The study is investigator-initiated and the AMC, as sponsor, will remain owner of all data and have all publication rights. Results will be submitted for publication in a peer-reviewed international medical journal. Trial registration number: NTR6323; Pre-results.